The Innovative Leadership of Schools Administrators Affecting Learning Organization in School under Pathum Thani Primary Educational Service Area Office 2 - Phonsa, Manunya; Prasansaph, Wipada (Academic MCU Buriram Journal, 2025)
This research aims to study the level of innovative leadership, study the level of being a learning organization, study the relationship between innovative leadership, and study the innovative leadership of school administrators that affects being a learning organization of the school under the Office of the Primary Educational Service Area, Pathum Thani Area 2. The sample group consisted of 59 schools under the Pathum Thani Primary Educational Service Area Office 2 for the academic year 2024. Data were collected from 59 school directors, 59 deputy directors in charge of academic affairs or heads of academic departments, and 177 teachers, totaling 295 participants. The research instrument was a questionnaire with a reliability coefficient of 0.988. Data analysis utilized mean, percentage, standard deviation, Pearson’s correlation coefficient, and stepwise multiple regression analysis. The research results found that: 1. The overall level of innovative leadership of school administrators was high. 2. The overall level of learning organization in schools under the Pathum Thani Primary Educational Service Area Office 2 was high. 3. There was a very strong positive correlation between the innovative leadership of school administrators and the learning organization in schools under the Pathum Thani Primary Educational Service Area Office 2, with a correlation coefficient of 0.910. 4. The innovative leadership of school administrators significantly influenced the learning organization in schools under the Pathum Thani Primary Educational Service Area Office 2. Key contributing factors included creating an innovative organizational atmosphere, having a vision for change, and fostering creativity. These factors collectively explained 87.60% of the variance in the learning organization of schools, with statistical significance at the 0.01 level.